Sulfide solid electrolyte and preparation method thereof
By forming a Li3PO4 coating layer on the surface of Li6PS5Cl, the air stability problem of Li6PS5Cl was solved, the electrochemical window and battery energy density were improved, and the process energy consumption and cost were reduced.
Patent Information
- Application Number
- CN202511110911.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-08
- Publication Date
- 2025-12-09
AI Technical Summary
Li6PS5Cl sulfide solid electrolytes have poor air stability and are prone to releasing toxic H2S gas upon contact with moisture, leading to structural damage and performance degradation. Existing modification methods suffer from problems such as reduced ionic conductivity, high cost, or weak interfacial bonding.
A dense coating layer was formed on the surface of Li6PS5Cl using a temperature gradient-assisted solvent-mediated method with Li3PO4 coating. The chemical stability of Li3PO4 and its high lattice matching with Li6PS5Cl were utilized to block moisture and oxygen, inhibit hydrolysis reaction, and improve the electrochemical window.
It significantly improves the air stability and electrochemical window of Li6PS5Cl, reduces electron leakage, is suitable for high-voltage cathode material systems, significantly improves battery energy density, and reduces process energy consumption and cost.
Smart Images

Figure CN121097185A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of battery technology, and in particular to a sulfide solid electrolyte and its preparation method. Background Technology
[0002] Sulfide solid electrolytes are valued for their high ionic conductivity (up to 10 mS / cm) and low density (1.7–2.5 g / cm³). 3 Due to its high ionic conductivity and good compatibility with lithium metal, Li₆PS₅Cl (LPSC) is considered a core material for the commercialization of all-solid-state batteries. Among them, Li₆PS₅Cl (LPSC) is considered a core material for the commercialization of all-solid-state batteries because it combines high ionic conductivity (approximately 10 mS / cm) with a suitable electrochemical window (approximately 4.5 V vs. Li / Li₂). + Li6PS5Cl has become a research hotspot. However, its fatal flaw of poor air stability severely restricts its practical application: when Li6PS5Cl comes into contact with moisture, it easily releases toxic hydrogen sulfide (H2S) and generates byproducts such as Li2O and P2O5, leading to structural damage and performance degradation. For example, after only 20 minutes of exposure to humid air, Li6PS5Cl can release up to 98.99 cm³ of hydrogen sulfide. 3 / g of H2S gas far exceeds the safety threshold.
[0003] To address the air stability issue of Li6PS5Cl, current optimization methods mainly involve doping modification or surface coating, but both have significant drawbacks, such as:
[0004] Oxide doping modification: Doping Li6PS5Cl with oxides such as ZnO, Bi2O3, and Al2O3 can suppress hydrolysis by forming a passivation layer. However, oxide doping introduces additional grain boundaries, significantly reducing ionic conductivity (by more than 50%), and the process is complex and costly.
[0005] Surface coating technology: Commonly used coating materials include Al2O3, SiO2, and Li2O. However, the interfacial bonding between the coating layer formed by these materials and the Li6PS5Cl matrix is weak and they are prone to detachment. In addition, although coating with Li2O can improve stability, it is highly hygroscopic and will still fail after long-term exposure. Materials such as Al2O3 have limited blocking effect on H2S and cannot completely solve the toxicity problem.
[0006] Element substitution and structural design: P can be replaced with soft acid elements such as Ge, Sn, and Sb, or anions such as Cl and I can be introduced to expand the electrochemical window. However, rare metals (such as Ge) are expensive (germanium dioxide costs over 6 million yuan per ton), and their structural designs are complex, making it difficult to balance stability and ionic conductivity.
[0007] Polymer composite electrolytes: Li6PS5Cl is combined with polymers (such as polyethylene oxide and polyvinyl alcohol) to improve interfacial contact by utilizing the flexibility of the polymer. However, polymers are prone to decomposition at high temperatures, limiting the battery operating temperature (usually <80℃), and the ionic conductivity of the composite material (<1mS / cm) is much lower than that of pure Li6PS5Cl electrolyte.
[0008] Therefore, existing technologies still need to be improved and developed. Summary of the Invention
[0009] In view of the shortcomings of the prior art, the purpose of this invention is to provide a sulfide solid electrolyte and its preparation method, which aims to solve the problem of poor air stability of Li6PS5Cl.
[0010] The technical solution of the present invention is as follows:
[0011] In a first aspect, the present invention provides a sulfide solid electrolyte, wherein the sulfide solid electrolyte comprises a Li6PS5Cl core and a Li3PO4 coating layer covering the surface of the Li6PS5Cl core.
[0012] A second aspect of the present invention provides a method for preparing the sulfide solid electrolyte as described above, comprising the following steps:
[0013] A dispersion is provided, the dispersion comprising Li6PS5Cl, Li3PO4 and an organic solvent, the organic solvent comprising at least one of xylene and butyl acetate;
[0014] The dispersion was placed in a sealed container, the bottom of the sealed container was heated and the top of the sealed container was cooled, so that a temperature gradient was formed in the vertical direction of the dispersion in the sealed container. After stirring, the sulfide solid electrolyte was obtained.
[0015] A third aspect of the present invention provides a method for preparing the sulfide solid electrolyte as described above, comprising the following steps:
[0016] Li6PS5Cl, Li3PO4 and an organic solvent were placed in a sealed container and dispersed. The bottom of the sealed container was heated and the top of the sealed container was cooled to create a temperature gradient in the vertical direction. After stirring, the sulfide solid electrolyte was obtained.
[0017] The organic solvent includes at least one of xylene and butyl acetate.
[0018] Optionally, in the dispersion, the mass ratio of Li3PO4 to Li6PS5Cl is (0.25–2):100.
[0019] Optionally, in the dispersion, the mass ratio of Li3PO4 to Li6PS5Cl is (0.25~1):100.
[0020] Optionally, the stirring speed is 50 to 200 rpm.
[0021] Optionally, the temperature of the heat source used for heating is 100–200°C.
[0022] Optionally, the temperature of the cold source used for refrigeration is -5℃ to 5℃.
[0023] Optionally, the sealed container includes a sealed container body and a sealing cap;
[0024] The steps of placing the dispersion in a sealed container, heating the bottom of the container, and cooling the top to create a temperature gradient in the vertical direction, followed by stirring, to obtain the sulfide solid electrolyte specifically include:
[0025] Place the dispersion in the sealed container body, and then seal it with a sealing cap to keep the dispersion in the sealed container.
[0026] Place the heat source at the bottom of the sealed container, and surround the cold source on the side of the sealed container at a predetermined distance from the top to the main body of the container. Set the temperature of the heat source to 100-200℃ and the temperature of the cold source to -5℃-5℃. Turn on the heat source and the cold source. Once the temperatures of the heat source and the cold source reach their respective set values, proceed with the following steps:
[0027] Step A: Stir the dispersion at a speed of 50-200 rpm for 15-30 minutes, then stop stirring for a certain period of time to allow the temperatures of the cold source and the heat source to return to their respective set values.
[0028] Step B: Repeat step A twice to obtain the reaction solution;
[0029] Step C: Stop cooling and heating, stir at 50-200 rpm until the temperature of the reaction liquid is at room temperature, centrifuge and dry to obtain the sulfide solid electrolyte.
[0030] Optionally, the distance between the liquid level of the dispersion and the top of the container interior is 1–2 cm; and / or,
[0031] The heat source is a heater, and the sealed container is placed on the heater; and / or,
[0032] The cold source is a condenser tube that continuously supplies an organic solvent at -5°C to 5°C. The organic solvent includes at least one of xylene and butyl acetate. The condenser tube surrounds the side area of the sealed container at a predetermined distance from the top of the sealed container to the main body of the sealed container.
[0033] Beneficial Effects: In this invention, the Li3PO4 coating layer effectively blocks moisture and oxygen, inhibiting the hydrolysis reaction of Li6PS5Cl. Compared to traditional Al2O3 coating, the Li3PO4 coating layer in this invention has a high lattice matching degree with Li6PS5Cl and strong interfacial bonding, effectively preventing secondary reactions caused by detachment. Furthermore, the introduction of Li3PO4 can act as a barrier layer or inhibit the redox reaction of Li6PS5Cl through surface chemical passivation mechanisms (forming stable layers such as Li2O or P2O5), increasing the electrochemical window from ~4.5V for Li6PS5Cl materials to >5.0V (vs. Li / Li). + It can also reduce electron leakage, making it very suitable for high-voltage cathode materials (such as NCM811) systems, and can significantly improve battery energy density. Attached Figure Description
[0034] Figure 1 This is a flowchart illustrating the preparation process of sulfide solid electrolytes.
[0035] Figure 2 This is a schematic diagram of the cylindrical sealed container, heater, and condenser used in Example 1.
[0036] Figure 3 This is a schematic diagram of the preparation process of the sulfide solid electrolyte in Example 1.
[0037] Figure 4 The image shows the XRD pattern of the sulfide solid electrolyte in Example 3.
[0038] Figure 5 The graph shows the LSV test results of different sulfide solid electrolytes in Example 3, where (a) is LPSC@Li3PO4-1% and (b) is LPSC. Detailed Implementation
[0039] This invention provides a sulfide solid electrolyte and its preparation method. To make the objectives, technical solutions, and effects of this invention clearer and more explicit, the invention is further described in detail below. It should be understood that the specific embodiments described herein are only for explaining the invention and are not intended to limit the invention.
[0040] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used in this specification is for the purpose of describing particular embodiments only and is not intended to be limiting of the invention.
[0041] The terms used in this document, such as “vertical,” “horizontal,” “up,” “down,” “left,” “right,” and similar expressions, are for illustrative purposes only and do not represent the only possible implementation.
[0042] In this invention, unless otherwise explicitly specified and limited, "above" or "below" the second feature can mean that the first feature is in direct contact with the second feature, or that the first feature is in indirect contact with the second feature through an intermediate medium. Furthermore, "above," "over," and "on top" of the second feature can mean that the first feature is directly above or diagonally above the second feature, or simply that the first feature is at a higher horizontal level than the second feature. "Below," "below," and "under" the second feature can mean that the first feature is directly below or diagonally below the second feature, or simply that the first feature is at a lower horizontal level than the second feature.
[0043] If the embodiments of the present invention involve descriptions such as "first" or "second", such descriptions are for descriptive purposes only and should not be construed as indicating or implying their relative importance or implicitly specifying the number of technical features indicated.
[0044] This invention provides a sulfide solid electrolyte, wherein the sulfide solid electrolyte includes a Li6PS5Cl core and a Li3PO4 coating layer (also referred to as a Li3PO4 shell) covering the surface of the Li6PS5Cl core.
[0045] In this embodiment of the invention, the Li3PO4 (lithium phosphate) coating layer can effectively block moisture and oxygen, inhibiting the hydrolysis reaction of Li6PS5Cl. Compared with traditional Al2O3 coating, the Li3PO4 coating layer in this invention has a high lattice matching degree with Li6PS5Cl (lattice constant difference <5%) and strong interfacial bonding, which can effectively avoid secondary reactions caused by delamination. In addition, Li3PO4 itself has high chemical stability (thermal decomposition temperature >800℃). The introduction of Li3PO4 can act as a barrier layer to prevent the oxidation reaction between Li6PS5Cl and the positive electrode active material (such as NCM) under high voltage. The oxygen in Li3PO4 may combine with the sulfur vacancies on the surface of Li6PS5Cl to form a Li2O / P2O5 composite passivation layer. Through the surface chemical passivation mechanism, the oxidation and decomposition of Li6PS5Cl is inhibited, thereby increasing the electrochemical window from ~4.5V of Li6PS5Cl material to >5.0V (vs. Li / Li + It is well-suited for high-voltage cathode material systems (such as NCM811), significantly improving battery energy density.
[0046] The introduction of Li3PO4 can also reduce electron leakage. Specifically, the insulating properties of Li3PO4 can suppress electronic short circuits between Li6PS5Cl and the electrode, preventing electrons from directly penetrating the electrolyte and triggering decomposition reactions under high voltage. Moreover, the high lattice matching degree between the Li3PO4 coating layer and Li6PS5Cl (lattice constant difference <5%) can protect the ion transport path, reduce interfacial ion transport resistance, and enable ions to participate in the reaction more efficiently, thereby reducing the occurrence of side reactions under the same voltage.
[0047] This invention also provides a method for preparing the sulfide solid electrolyte as described above, comprising the following steps:
[0048] A dispersion is provided, the dispersion comprising Li6PS5Cl, Li3PO4 and an organic solvent, the organic solvent comprising at least one of xylene and butyl acetate;
[0049] The dispersion is placed in a sealed container (a sealed container is used to avoid leakage and safety risks), the bottom of the sealed container is heated and the top of the sealed container is cooled, so that a temperature gradient is formed in the vertical direction of the dispersion in the sealed container. After stirring, the sulfide solid electrolyte is obtained.
[0050] This invention also provides another method for preparing the sulfide solid electrolyte as described above, comprising the following steps:
[0051] Li6PS5Cl, Li3PO4, and an organic solvent are placed in a sealed container and dispersed (specifically, stirring can be used to ensure uniform dispersion of Li3PO4, while the low surface tension of the organic solvent can further promote uniform dispersion of Li3PO4). The bottom of the sealed container is heated, and the top of the sealed container is cooled, so that a temperature gradient is formed in the vertical direction in the dispersion in the sealed container. After stirring, the sulfide solid electrolyte is obtained; the organic solvent includes at least one of xylene and butyl acetate.
[0052] This invention provides a temperature gradient-assisted solvent-mediated coating method that achieves Li3PO4 coating by creating a gradient temperature field through bottom heating and top cooling. Furthermore, the gradient temperature field also drives the evaporation-condensation cycle of an organic solvent (at least one of xylene and butyl acetate), further promoting the uniform dispersion of Li6PS5Cl and Li3PO4 powders, and the Li3PO4 coating. Through organic solvent-mediated uniform dispersion, this invention forms a dense and continuous coating layer of Li3PO4 on the surface of Li6PS5Cl, possessing both physical barriers and chemical stability. This overcomes the limitations of traditional high-temperature sintering or vapor deposition processes, avoiding material degradation caused by high temperatures. Simultaneously, the temperature gradient achieves efficient, low-energy-consumption uniform coating, significantly reducing process costs (energy consumption reduced by more than 30%).
[0053] Specifically, on the one hand, this invention employs temperature gradient-assisted solvent-mediated coating, utilizing the coupling effect of thermodynamics and kinetics, mainly including the following three aspects:
[0054] (1) Temperature gradient drives the difference in diffusion rate
[0055] According to Fick's second law, temperature gradients significantly affect the diffusion coefficient. In the high-temperature region (bottom), the thermal motion of material molecules intensifies, significantly increasing the diffusion coefficient of Li3PO4 particles and driving them to migrate to the low-temperature region. Conversely, in the low-temperature region (top), the molecular motion on the Li6PS5Cl surface slows down due to the decreased temperature, creating concentration gradient-driven deposition conditions.
[0056] (2) Surface energy regulation and interfacial reaction: In the high-temperature region, the surface energy of Li6PS5Cl increases, and the surface atomic activity is enhanced, which promotes the adsorption and nucleation of Li3PO4 particles on its surface. In the low-temperature region, it is conducive to the directional growth of Li3PO4 crystals and the formation of a dense coating layer.
[0057] (3) Synergistic effect of thermal convection and forced stirring: The natural convection (heat rises, cold sinks) caused by the temperature gradient and the forced convection of mechanical stirring work together to break the thermal stratification, so that Li3PO4 particles can be uniformly deposited on the surface of Li6PS5Cl, avoiding local concentrations that are too high or too low.
[0058] On the other hand, temperature gradient-assisted solvent-mediated coating affects the phase transformation and crystallization behavior of materials, mainly in the following aspects:
[0059] (1) Dissolution-recrystallization of Li3PO4
[0060] In the high-temperature region, some Li3PO4 may dissolve in the Li6PS5Cl matrix to form a liquid precursor. As the temperature gradient migrates to the low-temperature region, the supersaturation increases, inducing Li3PO4 to recrystallize and deposit on the surface of Li6PS5Cl, forming a uniform coating layer.
[0061] (2) Surface activation and chemical bonding of Li6PS5Cl
[0062] High temperature intensifies the atomic vibrations on the Li6PS5Cl surface, increases surface defects, enhances the interfacial interaction with Li3PO4, and improves the adhesion of the coating layer.
[0063] Polar solvents (such as water and ethanol) readily react with Li6PS5Cl, causing hydrolysis or side reactions that damage the Li6PS5Cl structure. This invention uses at least one of xylene and butyl acetate as the dispersion medium (dispersion solvent). On one hand, its low reactivity ensures the stability of the coating process and simplifies subsequent processing steps; on the other hand, its low surface tension promotes the uniform deposition and adsorption of Li3PO4 on the Li6PS5Cl surface; furthermore, it is a non-polar solvent or a weakly polar solvent, effectively avoiding the structural damage to Li6PS5Cl caused by the reaction of polar solvents (such as water and ethanol) with Li6PS5Cl.
[0064] In summary, the preparation method provided by this invention uses temperature gradient driven dispersion, requires no complex equipment, reduces energy consumption by more than 30%, uses low-cost organic solvents (e.g., xylene costs about $5 / kg), and the coating process does not require high-temperature sintering or vapor deposition, thus avoiding high energy consumption and the risk of material degradation.
[0065] In some embodiments, the mass ratio of Li3PO4 to Li6PS5Cl in the dispersion is (0.25 to 2):100, for example, it can be 0.25:100, 0.5:100, 0.8:100, 1:100, 1.2:100, 1.5:100, 1.8:100 or 2:100.
[0066] This ratio ensures that the ionic conductivity of the sulfide electrolyte obtained after coating is not significantly reduced compared to Li6PS5Cl (with a retention rate of at least 90%), which is significantly better than oxide doping (ionic conductivity reduction of 40% to 60%) or polymer composite (ionic conductivity reduction of >90%).
[0067] In other words, this ratio ensures that while significantly improving air stability (reducing H2S emissions by 90%), ionic conductivity is maintained to the maximum extent (reduction ≤10%). Traditional coating materials (such as Al2O3) require high coating amounts to achieve the stabilizing effect, but this leads to a significant decrease in ionic conductivity (reduction of more than 40%). This invention achieves the stabilizing effect with a low coating amount, thus balancing performance and practicality.
[0068] In some embodiments, the mass ratio of Li3PO4 to Li6PS5Cl in the dispersion is (0.25 to 1):100.
[0069] In some embodiments, the stirring speed is 50 to 200 rpm, for example, 50 rpm, 60 rpm, 70 rpm, 80 rpm, 90 rpm, 100 rpm, 120 rpm, 150 rpm, 180 rpm or 200 rpm.
[0070] In some embodiments, the temperature of the heat source used for heating is 100-200°C, for example, it can be 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, 190°C or 200°C.
[0071] In some embodiments, the temperature of the cold source used for refrigeration is -5℃ to 5℃, for example, it can be -5℃, -4℃, -3℃, -2℃, -1℃, 0℃, 1℃, 2℃, 3℃, 4℃ or 5℃, etc.
[0072] In some embodiments, the sealed container includes a sealed container body and a sealing cap (specifically, the sealed container may be a cylindrical sealed container, a cuboid sealed container, etc.).
[0073] The steps of placing the dispersion in a sealed container, heating the bottom of the container, and cooling the top to create a temperature gradient in the vertical direction, followed by stirring, to obtain the sulfide solid electrolyte specifically include:
[0074] Place the dispersion in the sealed container body, and then seal it with a sealing cap to keep the dispersion in the sealed container.
[0075] Place the heat source at the bottom of the sealed container, and surround the cold source on the side of the sealed container at a predetermined distance from the top to the main body of the container. Set the temperature of the heat source to 100-200℃ and the temperature of the cold source to -5℃-5℃. Once the temperatures of the heat source and the cold source reach their respective set values, proceed with the following steps:
[0076] Step A: Stir the dispersion at a speed of 50-200 rpm for 15-30 minutes, then stop stirring for a certain period of time to allow the temperatures of the cold source and the heat source to return to their respective set values.
[0077] Step B: Repeat step A twice to obtain the reaction solution;
[0078] Step C: Stop cooling and heating, stir at 50-200 rpm until the temperature of the reaction liquid is at room temperature, centrifuge and dry to obtain the sulfide solid electrolyte.
[0079] Stirring in steps A and B allows Li3PO4 in the dispersion to be deposited more uniformly on the surface of Li6PS5Cl.
[0080] In some embodiments, the distance between the liquid surface of the dispersion and the top of the container is 1 to 2 cm (e.g., 1 cm, 1.5 cm, or 2 cm, etc.).
[0081] In some embodiments, the heat source is a heater (e.g., a flat plate heater), and the sealed container is placed on the heater.
[0082] In some embodiments, the cold source is a condenser tube that continuously supplies an organic solvent at -5°C to 5°C, the organic solvent including at least one of xylene and butyl acetate, the condenser tube being surrounded on the side of the container at a predetermined distance from the top of the container to the container body.
[0083] The liquid flowing into the condenser is the same as the organic solvent in the dispersion to prevent leakage from affecting the internal environment.
[0084] Specifically, taking xylene as an example of an organic solvent, such as Figure 1 As shown, the preparation method of the sulfide solid electrolyte includes the following steps:
[0085] S1. Add Li6PS5Cl, Li3PO4 and xylene to the sealed container body, then cover it with a sealing cap to seal it, place it on a heater with a stirrer, and wrap a serpentine condenser around the side area from the top of the sealed container to the sealed container body at a predetermined distance.
[0086] S2. Turn on the stirrer for 15-30 minutes to fully disperse Li6PS5Cl and Li3PO4, then turn off the stirrer.
[0087] S3. Set the heater temperature to 100-200℃, continuously introduce xylene at -5℃ to 5℃ into the serpentine condenser, and wait for the heater and the serpentine condenser to reach their respective set temperatures.
[0088] S4. Turn on the stirrer for 15-30 minutes, then turn it off and wait for the temperature of the heater and the serpentine condenser to reach their respective set values. Repeat this operation three times. Turn off the heater and stop the flow of xylene at -5℃ to 5℃. Continue stirring until room temperature, centrifuge and dry to obtain the sulfide solid electrolyte.
[0089] The stirring speed used in steps S2 and S4 is described above.
[0090] The present invention will be further described below through specific embodiments.
[0091] In the following examples, xylene (CAS No.: 1330-20-7) was purchased from Shandong Xinheng Chemical Co., Ltd.
[0092] Example 1
[0093] This embodiment provides a method for preparing a sulfide solid electrolyte, comprising the following steps:
[0094] (1) As Figure 2 and Figure 3 As shown, Li6PS5Cl (i.e., LPSC), Li3PO4 and xylene were added to the cylindrical sealed container body 1 (its dimensions are: height h is 50cm, inner diameter is 10cm, and the thickness of the sealing cap is negligible). Then, the sealing cap 2 was put on to seal the container. The container was placed on a heater 3 with a stirrer. Without turning on the heater, the container was stirred at 100 rpm for 30 minutes to fully disperse LPSC and Li3PO4 and form a dispersion. Then, the stirring was stopped.
[0095] The distance between the liquid surface of the dispersion and the top of the inner part of the cylindrical sealed container is 2 cm. The total mass percentage of LPSC and Li3PO4 in the dispersion is 50%, and the mass ratio of Li3PO4 to LPSC is 0.25:100.
[0096] (2) A serpentine condenser tube 4 is fitted on the side area from the top of the cylindrical sealed container to 1 / 4 of the height of the cylindrical sealed container body, that is, the vertical height h1 of the serpentine condenser tube is 12.5cm.
[0097] (3) Set the heater temperature to 150℃ and turn on the heater. Then, continuously pass cold xylene (temperature -5℃) through the serpentine condenser. When the temperature of the heater control panel 31 reaches the set value of 150℃ and the temperature of the condenser reaches -5℃, proceed with the following steps:
[0098] Step A: Turn on the stirrer and stir at 100 rpm for 30 minutes, then stop stirring for a certain period of time (to allow the dispersion to stop flowing and for the actual temperature of the heater and the actual temperature of the condenser to return to 150℃ and -5℃ respectively).
[0099] Step B: Repeat step A twice (i.e., perform the "turn on the stirrer - stir - stop the stirrer" process three times in total) to obtain the reaction liquid;
[0100] Step C: Stop heating, stop the flow of xylene into the condenser, turn on the stirrer, and continue stirring at 100 rpm until the temperature of the reaction liquid reaches room temperature. Centrifuge, and dry under vacuum at 160°C for 12 minutes to obtain the sulfide solid electrolyte (denoted as LPSC@Li3PO4-0.25%).
[0101] Example 2
[0102] This embodiment provides a method for preparing a sulfide solid electrolyte, which differs from Example 1 only in that the mass ratio of Li3PO4 to LPSC in the dispersion is 0.5:100, and the resulting sulfide solid electrolyte is denoted as LPSC@Li3PO4-0.5%.
[0103] Example 3
[0104] This embodiment provides a method for preparing a sulfide solid electrolyte, which differs from Example 1 only in that:
[0105] In the dispersion, the mass ratio of Li3PO4 to LPSC is 1:100, and the resulting sulfide solid electrolyte is denoted as LPSC@Li3PO4-1%.
[0106] Example 4
[0107] This embodiment provides a method for preparing a sulfide solid electrolyte, which differs from Example 1 only in that:
[0108] In the dispersion, the mass ratio of Li3PO4 to LPSC is 2:100, and the resulting sulfide solid electrolyte is denoted as LPSC@Li3PO4-2%.
[0109] test:
[0110] The sulfide solid electrolytes prepared in Examples 1-4 were subjected to X-ray diffraction (XRD) tests. The specific operating steps are as follows:
[0111] 1. Powder Sample Preparation
[0112] In an inert gas (such as argon) glove box (to avoid sample oxidation or structural damage), the sulfide solid electrolyte is ground until the particle size is uniform (passes through a 200-mesh sieve, particle size ≤75μm), and there is no grainy feel to the touch, similar to the texture of flour, in order to reduce preferred orientation and enhance the intensity of diffraction peaks.
[0113] Then, the positive pressure method is used to fill the powder into the groove of the glass sample holder, and the glass plate is used to compact it until the surface is flat and flush with the groove to ensure the uniformity of the sample.
[0114] 2. Instrument Setup and Testing Procedure
[0115] 1) Instrument initialization
[0116] Circulating water system: Ensure water temperature is 20℃ and water pressure is 0.4MPa to prevent equipment from overheating or being damaged.
[0117] Software startup: Open the PC-based XRD control software (such as Rigaku Ultimate IV or DIFFRAC measurement system), initialize the goniometer, and confirm that the sample chamber door is closed.
[0118] 2) Parameter settings
[0119] Scanning range: The standard wide-angle test range is 5° to 90°, with a step size of 0.02° and a scanning speed of 5° / min (adjusted according to the crystallinity of the sample).
[0120] Slit width: entrance slit is 0.2-0.6 mm, detector slit is 3-8 mm, optimizing resolution and signal-to-noise ratio.
[0121] X-ray conditions: Copper target Kα rays The voltage is 40kV and the current is 30mA to ensure clear diffraction peaks.
[0122] 3) Sample loading and testing
[0123] Sample loading procedure: Gently open the sample chamber door, insert the sample holder into the slot, ensuring the sample surface is facing up and centered, gently close the door and confirm that the closing indicator light is on.
[0124] Start the test: Click "Start" to start the scan. Wait for the software to indicate completion and save the data (e.g., RAW or TXT format).
[0125] The XRD pattern of the sulfide solid electrolyte in Example 3 is shown below. Figure 4 As shown, this demonstrates that the Li3PO4 coating did not negatively affect the crystal phase of LPSC. Furthermore, the XRD results of the sulfide solid electrolytes in Examples 1, 2, and 4 are essentially the same as those of the sulfide solid electrolyte in Example 3.
[0126] The sulfide solid electrolytes prepared in Examples 1 to 4 were subjected to linear sweep voltammetry (LSV) testing. The specific operating steps are as follows:
[0127] 1. Sample preparation and electrode assembly
[0128] 1) Tableting
[0129] Pure LPSC powder and LPSC@Li3PO4-1% powder prepared in Example 3 were poured into a mold with a diameter of 10 mm and pre-compressed for 60 seconds with a pressure of 350 MPa to ensure compactness (thickness controlled at 2 mm). The integrity of the tablet was checked to avoid cracks or edge breakage, and LPSC tablets and LPSC@Li3PO4-1% tablets were obtained.
[0130] 2) Electrode assembly
[0131] Under inert gas (argon) protection (to prevent secondary oxidation), carbon-coated aluminum foil was placed on both sides of the LPSC sheet and the LPSC@Li3PO4-1% sheet as ion blocking electrodes. A steel kit was used to maintain pressure during the test to ensure good contact between the electrodes and the electrolyte.
[0132] 2. LSV test parameter settings
[0133] Scan range: Covers the redox peak potential range, 0–5.6V vs. RHE (avoiding lithium metal dissolution at negative potentials).
[0134] Scan rate: Initially set to 5mV / s (glassy carbon electrode), which can be reduced to 2mV / s if the current signal is weak.
[0135] Equilibrium time: Allow the device to stand still for 30 seconds before each scan to eliminate polarization effects.
[0136] Multi-inflection point setting: The multi-segment scanning mode of "starting potential → inflection point 1 → inflection point 2 → starting potential" is adopted to avoid potentials exceeding the range.
[0137] 3. Test Operation Steps
[0138] Instrument calibration: Use a standard solution (such as KCl solution) to calibrate the reference electrode potential.
[0139] Battery connection: Connect the assembled electrodes to the electrochemical workstation, and connect the working electrode, reference electrode, and counter electrode.
[0140] Pretreatment: Perform 3 to 5 cycles of cyclic voltammetry (CV) scans (1 mV / s) to activate the electrode surface.
[0141] LSV test: Start the LSV scan and record the current-potential curve. If the curve does not start from 0 (due to the influence of double-layer current), the background current can be eliminated by a slow CV (1mV / s) pre-scan.
[0142] 4. Data Processing and Analysis
[0143] 1) Peak potential identification
[0144] Oxidation peak (anodide): The inflection point where the current changes from negative to positive corresponds to the oxidation initiation potential (Epa).
[0145] Reduction peak (cathode): The inflection point where the current changes from positive to negative corresponds to the reduction initiation potential (Epc).
[0146] Electrochemical window: the difference between Epa (maximum oxidation potential) and Epc (minimum reduction potential).
[0147] The results of LPSC and LPSC@Li3PO4-1% in Example 3 are as follows: Figure 5 As shown, the electrochemical window between the oxidation and reduction potentials increases after LPSC is coated with Li3PO4. The LSV test results of the sulfide solid electrolytes in Examples 1, 2, and 4 are basically the same as those of LPSC@Li3PO4-1% in Example 4.
[0148] Sulfide solid electrolyte powder and LPSC powder from Examples 1 to 4 were taken respectively. Each example's sulfide electrolyte powder and LPSC powder were divided into 5 equal portions. One portion was directly tested for ionic conductivity (i.e., placed in a 5% humidity stable test chamber for 0 hours). The other four portions were placed in a 5% humidity stable test chamber for 2 hours, 4 hours, 8 hours, and 24 hours respectively. The corresponding powders were then taken out to test their ionic conductivity. The specific steps are as follows:
[0149] (1) Sample preparation
[0150] The sulfide solid electrolyte powder is cold-pressed into sheets under a pressure of 500 MPa, with a thickness of about 0.1 to 1 mm and a diameter of 10 to 14 mm.
[0151] (2) Electrochemical impedance spectroscopy (EIS)
[0152] The sample is held in place using a blocking electrode (such as stainless steel or sputtered metal film), and an AC voltage (amplitude 10mV, frequency range 1MHz to 0.1Hz) is applied.
[0153] The bulk resistance R is obtained by fitting the semicircular intercept in the high-frequency region using EIS. bulk The low-frequency region reflects the interfacial resistance and the double-layer effect.
[0154] (3) Geometric parameter measurement
[0155] Thickness (L): The thickness of the compressed tablet is measured directly using a micrometer;
[0156] Area (A): Calculated based on the electrode diameter;
[0157] According to the formula Calculate the ionic conductivity of the corresponding material.
[0158] Table 1. Results of Ion Conductivity Test
[0159]
[0160]
[0161] The ionic conductivity test results above show that the air stability of LPSC is significantly improved after coating with Li3PO4. As the coating amount increases, the air stability gradually improves as well, but the initial ionic conductivity decreases noticeably over time. This is because Li3PO4 is an electronically insulating material (with extremely low electronic conductivity), and its coating layer hinders the transport path of lithium ions within the electrolyte. With increasing coating amount, the thickness of the Li3PO4 coating layer increases, leading to partial blockage of ion transport channels and thus reducing the overall ionic conductivity. However, by controlling the coating amount, air stability can be significantly improved while maintaining an ionic conductivity greater than 90% of that of LSPC.
[0162] It should be understood that the application of the present invention is not limited to the examples above. Those skilled in the art can make improvements or modifications based on the above description, and all such improvements and modifications should fall within the protection scope of the appended claims.
Claims
1. A sulfide solid electrolyte, characterized in that, The sulfide solid electrolyte comprises a Li6PS5Cl core and a Li3PO4 coating layer covering the surface of the Li6PS5Cl core.
2. A method for preparing the sulfide solid electrolyte according to claim 1, characterized in that, Includes the following steps: A dispersion is provided, the dispersion comprising Li6PS5Cl, Li3PO4 and an organic solvent, the organic solvent comprising at least one of xylene and butyl acetate; The dispersion was placed in a sealed container, the bottom of the sealed container was heated and the top of the sealed container was cooled, so that a temperature gradient was formed in the vertical direction of the dispersion in the sealed container. After stirring, the sulfide solid electrolyte was obtained.
3. A method for preparing the sulfide solid electrolyte according to claim 1, characterized in that, Includes the following steps: Li6PS5Cl, Li3PO4 and an organic solvent were placed in a sealed container and dispersed. The bottom of the sealed container was heated and the top of the sealed container was cooled to create a temperature gradient in the vertical direction. After stirring, the sulfide solid electrolyte was obtained. The organic solvent includes at least one of xylene and butyl acetate.
4. The preparation method according to claim 2 or 3, characterized in that, In the dispersion, the mass ratio of Li3PO4 to Li6PS5Cl is (0.25~2):
100.
5. The preparation method according to claim 2 or 3, characterized in that, In the dispersion, the mass ratio of Li3PO4 to Li6PS5Cl is (0.25~1):
100.
6. The preparation method according to claim 2 or 3, characterized in that, The stirring speed is 50-200 rpm.
7. The preparation method according to claim 2 or 3, characterized in that, The heating uses a heat source with a temperature of 100–200°C.
8. The preparation method according to claim 2 or 3, characterized in that, The temperature of the cold source used for refrigeration is -5℃ to 5℃.
9. The preparation method according to claim 2 or 3, characterized in that, The sealed container includes a sealed container body and a sealing cap; The steps of placing the dispersion in a sealed container, heating the bottom of the container, and cooling the top to create a temperature gradient in the vertical direction, followed by stirring, to obtain the sulfide solid electrolyte specifically include: Place the dispersion in the sealed container body, and then seal it with a sealing cap to keep the dispersion in the sealed container. Place the heat source at the bottom of the sealed container, and surround the cold source on the side of the sealed container at a predetermined distance from the top to the main body of the container. Set the temperature of the heat source to 100-200℃ and the temperature of the cold source to -5℃-5℃. Turn on the heat source and the cold source. Once the temperatures of the heat source and the cold source reach their respective set values, proceed with the following steps: Step A: Stir the dispersion at a speed of 50-200 rpm for 15-30 minutes, then stop stirring for a certain period of time to allow the temperatures of the cold source and the heat source to return to their respective set values. Step B: Repeat step A twice to obtain the reaction solution; Step C: Stop cooling and heating, stir at 50-200 rpm until the temperature of the reaction liquid is at room temperature, centrifuge and dry to obtain the sulfide solid electrolyte.
10. The preparation method according to claim 9, characterized in that, The distance between the liquid level of the dispersion and the top of the container interior is 1–2 cm; and / or, The heat source is a heater, and the sealed container is placed on the heater; and / or, The cold source is a condenser tube that continuously supplies an organic solvent at -5°C to 5°C. The organic solvent includes at least one of xylene and butyl acetate. The condenser tube surrounds the side area of the sealed container at a predetermined distance from the top of the sealed container to the main body of the sealed container.
Citation Information
Cited By
Solid electrolyte with multi-layer coating structure, preparation method of solid electrolyte and battery
CN122073253A
